Learning Environment Management at Nanga Temalat National School Sarawak - Amran, Nur Fatin Najwa; Hashim, Nurul Farzana; Jumadi, Mohd Khairul Nizam; Mohamad Jamil, Norzaimah; Ibrahim, Noraini; Sagin, Cyrilyn; Husin, Mohd Razimi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Guru merupakan individu yang memainkan peranan penting dalam pengurusan alam pembelajaran. Pengurusan alam pembelajaran perlu bagi merangsang minat belajar kanak-kanak. Pengurusan alam pembelajaran penting bagi memenuhi masa yang diperuntukkan untuk mengajar dan juga memastikan objektif pembelajaran dan pengajaran tercapai serta menarik perhatian pelajar terhadap sebuah pengajaran. Sekolah Kebangsaan Nanga Temalat di Sarawak menjadi pilihan untuk melaksanakan kajian tentang pengurusan alam pembelajaran yang mana seorang responden adalah seorang guru daripada Sekolah Kebangsaan Nanga Temalat. Pengurusan alam pembelajaran perlu dilakukan sebelum PDP, semasa PDP dan selepas PDP. Kajian ini mendapati bahawa pengurusan alam pembelajaran yang mantap dan efektif adalah merupakan kunci utama dalam keberhasilan suatu pengajaran dan pembelajaran. Guru perlu menitikberatkan aspek pengurusan alam pembelajaran supaya minat setiap murid dapat dipupuk dengan lebih berkesan di samping dapat memastikan guru dapat menyampaikan maklumat kepada murid-murid dengan lebih lancar sekaligus guru juga dapat meningkatkan pencapaian setiap murid. Learning Environment Management at Nanga Temalat National School Sarawak Abstract: Teachers are individuals who play an important role in the management of the learning environment. Management of the learning environment is necessary to stimulate children's interest in learning. The management of the learning environment is important to meet the time allotted for teaching and also to ensure that learning and teaching objectives are achieved and attract students' attention to a lesson. Nanga Temalat National School in Sarawak was chosen to carry out a study on the management of the learning environment where one respondent was a teacher from Nanga Temalat National School. Learning environment management needs to be done before PDP, during PDP and after PDP. This study found that the management of a robust and effective learning environment is the main key to the success of teaching and learning. Teachers need to focus on the management aspect of the learning environment so that each student's interest can be nurtured more effectively while also being able to ensure that the teacher can convey information to the students more smoothly and at the same time the teacher can also improve the achievement of each student. Keywords: Learning, Learning Environment Management, SWOT.